Factors associated with the metabolically obese thin phenotype in Peruvian inhabitants - Guerra Valencia, Jamee; Torres Malca, Jenny Raquel; Talavera, Jesus E.; Zuzunaga-Montoya, Fiorella E.; De La Cruz Vargas , Jhony Alberto; Vera-Ponce, Víctor Juan (Medicina Clínica y Social, 2022)
Introduction: Patients with the lean metabolically obese (BMD) phenotype may present the same risk as the classic obese for developing long-term chronic diseases. However, the prevalence and the factors that are associated with it vary according to the population studied.Objective: to determine the prevalence and the factors associated with the BMD phenotype in Peru.Methods: Cross-sectional analytical study. Secondary analysis of the PERU MIGRANT study database. The associated factors that were considered were: age (30-44 years, 45-59 years, and 60 years and over), sex, socioeconomic status, level of education, migration, smoking, alcohol consumption and level of physical activity.Results: The prevalence of the BMD phenotype was 32.23% (95% CI 27.61-37.10). In the multivariate analysis, the male sex showed a 39% lower probability of presenting the BMD phenotype (PRa: 0.610; 95% CI 0.428-0.869; p=0.006), compared to the female sex. While belonging to the age groups between 45-59 years and 60 years and over presented 110.5% (PRa: 2.105; 95% CI 1.484-2.988; p
Keywords: obesity, metabolism, Epidemiologic Factors, Peru.